2003
DOI: 10.2170/jjphysiol.53.243
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of Muscle Spindles Enhances the Thixotropic Behavior of Rib Cage Respiratory Muscles.

Abstract: Rib cage inspiratory muscle contractions at a deep inflated position caused a subsequent increase in rib cage cross-sectional area at the end-expiratory phase. The increase in this area was enhanced by the activation of muscle spindles in the inspiratory muscles by a mechanical vibration combined with muscle contractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Inspiratory muscle conditioning based on the principles of muscle thixotropy acutely alters the end‐expiratory position of the respiratory system during resting breathing 6–11 . Thixotropy conditioning of inspiratory muscles involves inspiratory muscle contraction at an inflated or deflated lung volume because inspiratory muscles shorten and lengthen with lung inflation and deflation, respectively 12–15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspiratory muscle conditioning based on the principles of muscle thixotropy acutely alters the end‐expiratory position of the respiratory system during resting breathing 6–11 . Thixotropy conditioning of inspiratory muscles involves inspiratory muscle contraction at an inflated or deflated lung volume because inspiratory muscles shorten and lengthen with lung inflation and deflation, respectively 12–15 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Inspiratory muscle conditioning based on the principles of muscle thixotropy acutely alters the end-expiratory position of the respiratory system during resting breathing. [6][7][8][9][10][11] Thixotropy conditioning of inspiratory muscles involves inspiratory muscle contraction at an inflated or deflated lung volume because inspiratory muscles shorten and lengthen with lung inflation and deflation, respectively. [12][13][14][15] Conditioning performed below FRC, which corresponds to hold-long conditioning of inspiratory muscles, is followed by decreases in end-expiratory chest wall volume (Vcw); conditioning performed above FRC, which corresponds to hold-short conditioning of inspiratory muscles, is followed by increases in end-expiratory Vcw.…”
Section: Introductionmentioning
confidence: 99%
“…Conditioning for developing inspiratory muscle thixotropy involves inspiratory muscle contraction at an inflated or deflated lung volume (VL) (18,20,27). Inspiratory muscles include the diaphragm, the external intercostals, and the parasternal intercostals, and these muscles shorten and lengthen with lung inflation and deflation, respectively (3,(5)(6)(7).…”
mentioning
confidence: 99%
“…We have reported that inspiratory muscle conditioning based on the principles of muscle thixotropy acutely changes end-expiratory chest wall volume (Vcw) and lung volume in healthy humans and patients with chronic obstructive pulmonary disease (COPD) [6][7][8][9][10]. Thixotropy conditioning of inspiratory muscles involves inspiratory muscle contraction at an inflated or deflated lung volume [6][7][8][9][10].…”
mentioning
confidence: 99%
“…Thixotropy conditioning of inspiratory muscles involves inspiratory muscle contraction at an inflated or deflated lung volume [6][7][8][9][10]. Inspiratory muscles include the diaphragm, the external intercostals, and the parasternal intercostals, and these muscles shorten and lengthen with lung inflation and deflation, respectively [11][12][13][14].…”
mentioning
confidence: 99%